THE THERMODYNAMIC PROPERTIES OF THE ALLOYS OF THE SYSTEM SI-MG: UDC 541.122; 536.7 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
Thermochemical properties of alloys in system silicon-magnesium are defined by calorimetric method at 1200 K, and thermodynamic activities of components are modeled from liquidus coordinates.
Keywords: -